The Effects of Antepartum Depressive Symptoms on Postcesarean Opioid Consumption - Walker, Zachary; Perkins, Callie; Harper, Lorie; Jauk, Victoria; Szychowski, Jeff M.; Mazzoni, Sara (American Journal of Perinatology, 2020)
Objective The study aimed to test the hypothesis that higher Edinburgh Postnatal Depression Scale (EPDS) scores are associated with increased pain scores and opioid use during postpartum hospitalization following cesarean section.Study Design We conducted a retrospective cohort of English or Spanish-speaking women ≥18 years who had prenatal care for a singleton gestation and delivered by cesarean at ≥36 weeks within a tertiary center during 2017. Exclusions included women with fetal anomalies, intrauterine fetal demise, sickle cell disease, previously diagnosed pain disorders (e.g., chronic pain or fibromyalgia), substance use disorder (based on documented prescription or use of methadone or buprenorphine), or reoperation during hospital stay. Women without an EPDS recorded antenatally were also excluded. Major depressive symptoms (MDS) were defined as a documented antenatal EPDS ≥12. Women with and without MDS were compared, and multivariable linear regression models were generated to evaluate associations between MDS status and both pain scores and opioid use.Results Of the 891 women meeting other inclusion criteria, 676 (76%) had documented antenatal EPDS scores, and 104 (15.4%) of those had MDS. Women with MDS were more likely to be use tobacco and have general anesthesia for cesarean delivery, but groups were otherwise similar. Women with MDS reported higher daily and average pain scores postpartum (2.4 vs. 1.7 average; p < 0.001). Women with MDS used more morphine milligram equivalents (MME) each day during their postpartum hospitalization, leading to a higher total MME use (121 mg [60.5–214.5] vs. 75 mg [28.5–133.5], p < 0.001).Conclusion We found an association between antepartum depressive symptoms and acute pain after cesarean delivery leading to increased opioid use. Given the current focus on opioid stewardship, further research into this association, exploration of tailored pain control, and determining whether treatment of antepartum MDS reduces postpartum pain, and therefore opioid use, will be of the utmost priority.Key Points
Keywords: depression; opioid; antepartum; postpartum; pain score